PROBLEMS OF ENTREPRENEURSHIP DEVELOPMENT IN THE PRODUCTION SECTOR IN THE REPUBLIC OF KAZAKHSTAN - Utegenov Erkebulan Kakimovich; Zhanabayeva Zhanar Kairbekovna (Scientific Journal of Pedagogy and Economics, 2021)
The purpose of the article is to analyze the application of mechanisms for the development of entrepreneurship in the production sector of the regions of Kazakhstan and develop proposals for its improvement. The research uses General scientific research methods such as observation, description, analysis and synthesis, as well as comparative, formal-logical and other methods of cognition. Statistical data and data on projects of Damu entrepreneurship Development Fund JSC, which provides assistance in the creation and development of small and medium-sized business projects in Kazakhstan, were used as a research information base. This article demonstrates and analyzes current quantitative information on the number of enterprises in the field of small and medium-sized businesses in the regional and industry context. In order to lay the foundations for more inclusive, rational and sustainable growth, Kazakhstan needs to diversify its production and export structure, as well as reduce its dependence on extractive industries by switching to new high-productivity industries. In particular, Kazakhstan should continue reforms aimed at improving the business climate and laying the foundations for the development of entrepreneurship in the production sector, which is connected not so much with natural resources as with innovation and human capital. Every year in the country there is a positive dynamic of growth in the number of enterprises in the field of small and medium-sized businesses. The study also reviewed reviews of the international company OECD (Organization for economic cooperation and development (OECD). OECD, eng. Organization for Economic Co-operation and Development (OECD) – international economic organization of developed countries that recognize the principles of representative democracy and free market economy.) for 2016-2019. The forms and sources of financing are investigated, and the features of the development of small and mediumsized enterprises in the Republic of Kazakhstan in the production sector aimed at stimulating and supporting entrepreneurship and SME activities, including related areas of research and innovation are determined. Measures are proposed to minimize regulatory requirements and improve mechanisms for supporting and protecting domestic producers working in the conditions of Kazakhstan's entry into the Eurasian economic space.